Transformational leadership style to improve the performance of health workers at penfui health center and bakunase health center - Ximenes, Gracieth Tomas Correia Dias; Adu, Apris; Littik, Serlie K. A. (Public Health Risk Assesment Journal, 2025)
Background: Transformational leadership style is a way used by a leader in influencing, directing, encouraging and controlling subordinates in order to achieve organizational goals efficiently and effectively which has the ability to inspire and motivate followers for mutual success. Based on an initial survey conducted at the Bakunase Health Center and Penfui Health Center, it appears that the style used by leaders is the interaction of leaders with their subordinates, but the transformation style has not been applied optimally so that it can be seen from 10 health workers, 2 of them have low performance. The purpose of this study was to analyze the relationship between transformational leadership style and the performance of health workers at Bakunase Health Center and Penfui Health Center. Methods: This study employs a quantitative research design with a cross-sectional approach, utilizing purposive sampling to select 100 healthcare workers. Data were analyzed using the Chi-Square test. Findings: The findings reveal a significant relationship between transformational leadership and healthcare worker performance, with a p-value of 0.000 (p<0.05). These results indicate that transformational leadership is an essential factor in improving healthcare service quality and workforce efficiency. Conclusion: The study concludes that implementing transformational leadership practices can enhance nurse performance and healthcare service delivery. Novelty/Originality of this article: The novelty of this research lies in its empirical demonstration of the direct impact of transformational leadership on healthcare worker performance in a community health center setting, reinforcing the importance of leadership development in public health institutions.